Arjantin Tango Temel Hareketlerinin Anatomik Analizi - Altun, Rıza Özgür (Sosyal Bilimler Enstitüsü, 2019)
Arjantin tango; yalnızca bir dans, müzik veya kültür elemanı olarak görülmez. Arjantin'e göç edenlerin taşıdığı pek çok farklı kültürün harmanlanmasıyla oluşmuş, başlı başına bir kültürdür. Tango dansçıları, ekseriyetle, bu dansı sahnede veya herhangi bir dans pistinde yapıp bitirdiği bir dans türü gibi değil, tüm ömrü boyunca sürdürdüğü bir alışkanlık olarak benimserler. Uzun dönemler boyu devam eden bir itiyat haline dönüşmesi ise beraberinde çeşitli fiziksel sorumlulukları taşımaktadır. Anatomik olarak uygun olmayan hareketlerin, duruşların uzun vadede önemli sağlık sorunları yaratacağı aşikârdır. Bu çalışmada tango dansının yapı taşı olan, dansçıların sıklıkla kullandığı veya çok sık kullanılmasa dahi farklı dans türlerinde rastlanmayıp, tangoya özgü karakteristik yapıya sahip temel tango hareketleri olan postura, abrazo abierto, abrazo cerrado, paso adelante, paso atras, paso al costado, pivote, paso cruce, la cruzada, ocho adelante, ocho atras, sacada, giro, enganche, gancho, boleo, pasada, passivo levantar, planeo, volcada ve colgada anatomik olarak incelenerek eklem hareket açıklığı değerleri tespit edilip yazıya alındı ve çalışmanın ekinde bu eklem hareketlerinin yapılmasını sağlayan ana kas gruplarına dair egzersiz önerileri sunuldu. Hareketlerin incelendiği başlıkların, Arjantin'in resmi dili olan İspanyolca ve yerel argosu olan Lunfardo temelinde kalması ile alanda henüz sabitlenmemiş olan terminolojinin gelişmesine bir katkı sağlamak amaçlandı.

This study presents the anatomical analysis of basic Argentine Tango figures. Analysis contains range of motion of joints, related muscle groups, and showing them with Movement Staff Notation System (HPNS). In appendices, some exercises are suggested to support flexibility and strength for agonists and synergistic muscle groups working in the implementation of the tango movements analyzed. They will help to increase physical comfort of individuals who are considered to be physically healthy in long-term studies and will be able to play a facilitating role in solving physical problems that may discomfort the movement. Tango dancers often adopt this dance not just as a dance type that is done on stage or on any dance floor, but as a habit that dancer pursues throughout life. The transformation into long-term persistence carries various physical responsibilities. It is obvious that anatomically inappropriate movements and postures will cause significant health problems in the long term. Postura, abrazo abierto, abrazo cerrado, paso adelante, paso atras, paso al costado, pivote, paso cruce, la cruzada, ocho adelante, ocho atras, sacada, giro, enganche, gancho, boleo, pasada, passivo levantar, planeo, volcada, and colgada figures are analyzed. Some of these terms in this study that are called as basic tango movements are not used so frequently in dance but they are characteristic movements of tango dance and not used in other dance genres. The analyses are based on three dimensional images which are modeled on the photographs and these images were taken from the videos of the dances which were accepted as the founder and the most important instructor of the modern tango system by the Gustavo NAVEIRA and his partner Giselle NAVEIRA. A data pool that was total of 1706 photos, taken from sixty-five videos were analyzed for aforementioned basic movements. The dance sections in which the movements were observed were randomly selected, without any special aim. Analyzing the screenshot images from recorded videos during dance performances provided opportunity of seeing natural flow of movement in tango dance.
Anatomical Analysis Of Basic Argenitne Tango Figures
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 2019
Keywords: Bale ve Dans; Güzel Sanatlar; Sahne ve Görüntü Sanatlar; Egzersiz hareket teknikleri; Erkek dansçılar; Kas germe egzersizleri; Sosyal Latin dansları; İkili dans; Ballet and Dance; Fine Arts; Performing and Visual Arts; Exercise movement techniques; Male dancers; Muscle stretching exercises; Social Latin dance; Pas de deux